Microbial populations and the activity of the soil under agricultural and agricultural-pastoral systems - Lucizano Garcia, Martha Regina; Nahas, Ely [UNESP] (Taylor & Francis Ltd, 2012)
The effects of agricultural-pastoral and tillage practices on soil microbial populations and activities have not been systematically investigated. The effect of no-tillage (NT), no-tillage agricultural-pastoral integrated systems (NT-I) and conventional tillage (CT) at soil depths of 0-10, 10-20 and 20-30 cm on the microbial populations (bacteria and fungi), biomass-C, potential nitrification, urease and protease activities, total organic matter and total N contents were investigated. The crops used were soybean (in NT, NT-I and CT systems), corn (in NT and NT-I systems) and Tanner grass (Brachiaria sp.) (in NT-I system); a forest system was used as a control. Urease and protease activities, biomass-C and the content of organic matter and total N were higher (p < 0.05) in the forest soil than the other soils. Potential nitrification was significantly higher in the NT-I system in comparison with the other systems. Bacteria numbers were similar in all systems. Fungi counts were similar in the CT and forest, but both were higher than in NT. All of these variables were dependent on the organic matter content and decreased (p < 0.05) from the upper soil layer to the deeper soil layers. These results indicate that the no-tillage agricultural-pasture-integrated systems may be useful for soil conservation.
Keywords: urease activity; protease activity; potential nitrification; biomass-C; soil bacteria; soil fungal populations